EFFECT OF CURRENT RATIO, DEBT TO EQUITY RATIO AND SALES GROWTH ON FINANCIAL DISTRESS WITH RETURN ON ASSETS AS INTERVENING VARIABLE: Study on Mining Sector Companies Listed on the Indonesia Stock Exchange 2013-2020 Period - Sri Astuti; Devyanthi Sjarif (Universitas Indonesia Membangun, 2022)
The purpose of this study was to determine the effect of Current Ratio, Debt to Equity Ratio, and Sales Growth on Financial Distress with Return on Assets as an Intervening Variable. This study uses quantitative methods with descriptive and verification approaches. Testing the data in this study using the classical assumption test, as well as testing the hypothesis using path analysis, correlation coefficient tests, and coefficients of determination tests. Data processing using IBM SPSS 26.0 program. Based on the results of this study indicate that (1) Current Ratio has an effect on Financial Distress. (2) Debt to Equity Ratio has no effect on Financial Distress. (3) Sales Growth has no effect on Financial Distress. (4) Current Ratio has an effect on Return on Assets. (5) Debt to Equity Ratio has no effect on Return on Assets. (6) Sales Growth has no effect on Return on Assets. (7) Return on Assets has an effect on Financial Distress. (8) Current Ratio, Debt to Equity Ratio and Sales Growth have a simultaneous effect on Financial Distress. (9) Current Ratio, Debt to Equity Ratio and Sales Growth have a simultaneous effect on Return on Assets. (10) Current Ratio, Debt to Equity Ratio and Sales Growth have a simultaneous effect on Financial Distress with Return on Assets as an intervening variable.